2016
DOI: 10.18699/vj16.176
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of wheat (Triticum aestivum L.) plants-regenerants produced by anther culture

Abstract: 2 Стендский исследовательский центр Института сельскохозяйственных ресурсов и экономики, Латвийский сельскохозяйственный университет, Стенде, ЛатвияИзучено генетическое разнообразие растений-регенерантов пшеницы (Triticum aestivum L.), которые созданы методом культуры пыльников из гибридов, используемых в селекции этой культуры в Латвии. Метод проточной цитометрии применяли для определения плоидности каждого зеленого растения-регенеранта. В свою очередь, универсальным iPBS (inter primer binding sites) методом,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Regarding spontaneously doubled haploid plants, the situation is the opposite of the haploid plant. The results are supported by the findings of Grauda et al (2016) who showed that genotype significantly affected haploid plant and spontaneous doubled-haploid plants developed from green plants.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding spontaneously doubled haploid plants, the situation is the opposite of the haploid plant. The results are supported by the findings of Grauda et al (2016) who showed that genotype significantly affected haploid plant and spontaneous doubled-haploid plants developed from green plants.…”
Section: Discussionsupporting
confidence: 78%
“…However, both sporogenesis and gametogenesis of Arabidopsis thaliana were observed in flower buds exhibiting visual filament [26]. Using buds whose size correlated to a suitable stage of pollen development has been one of the crucial factors determining the success of in vitro microspore or anther culture [10], and different stages were required for different species [9,11]. Hence, flower buds of ≥ 1.6 mm in diameter presenting haploid unicellular microspore or bicellular pollen might be suitable and recommended for the haploid plant induction of J. curcas.…”
Section: Male and Female Gametophyte Development In Relation To Bud Diameter And Morphology Male Gametophyte (Pollen) Developmentmentioning
confidence: 99%
“…Accordingly, haploid and double haploid embryos are required, because they provide homozygous genotypes necessary for breeding programs [8]. Haploid embryos can be induced through anther [9] or unfertilized eggs [8]. An appropriate stage of microspore and embryo sac, which is one of the most critical parameters for the success of the haploid culture, varies among the species [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…MARCINIAK et al (2003) reported that hybrids were generally more responsive than their parents. CHAUDHARY et al (2003), GRAUDA et al (2016) and DAGUSTU (2008) found that respectively, additive, dominant, and epistatic gene effects play a role in the inheritance of androgenetic traits. Heterosis for anther response is changed from genotype to genotype (AL-ASHKAR, 2014).…”
Section: Introductionmentioning
confidence: 99%